2021
DOI: 10.3390/brainsci11010072
|View full text |Cite
|
Sign up to set email alerts
|

Applying Eye Movement Modeling Examples to Guide Novices’ Attention in the Comprehension of Process Models

Abstract: Process models are crucial artifacts in many domains, and hence, their proper comprehension is of importance. Process models mediate a plethora of aspects that are needed to be comprehended correctly. Novices especially face difficulties in the comprehension of process models, since the correct comprehension of such models requires process modeling expertise and visual observation capabilities to interpret these models correctly. Research from other domains demonstrated that the visual observation capabilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…This finding aligns with [14], which observed similar effects in simple process models with minimal complexity. As suggested by [47], process models varying in size and complexity could exhibit different cognitive load levels. Moreover, ref.…”
Section: Discussionmentioning
confidence: 99%
“…This finding aligns with [14], which observed similar effects in simple process models with minimal complexity. As suggested by [47], process models varying in size and complexity could exhibit different cognitive load levels. Moreover, ref.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, effects of EMME on performance measures imply changes in how observers process the instructional material. Litchfield et al (2010) for example showed that learners take longer to execute the task in the presence versus absence of the EMME, and Winter et al (2021) found that the EMME helped observers to execute the task. Conversely, effects of EMME on learning measures imply that the altered processing of the instructional material has longer-lasting consequences for the memory and task performance, showing later on in the absence of the EMME (see also Soderstrom & Bjork, 2015).…”
Section: Which Types Of Effects Did the Identified Studies Explore?mentioning
confidence: 99%